PENGARUH EKSTRAK BUAH Carica pubescens Lenne & K. Koch YANG TUMBUH DI BEBERAPA TEMPAT DI INDONESIA TERHADAP PENYEMBUHAN LUKA MUKOSA RONGGA MULUT - Kristanti, Risma Aprinda (El-Hayah : Jurnal Biologi, 2015)
The aim of this study is to examine the effect of Carica Â pubescens Lenne K. Koch extract to the epihtelialization on the wound healing of gingival mucosa and to examine the effect of C. pubescens extract from different region (Dieng and Cangar) to the epithelialization process.Twenty eight adult male albino rats were devided into four group, we created cutlet along 1 cm on the mandibular gingival mucosa below insisiv teeth. K1 group were treated with aquadest while K2 group were treated with C. pubescens extract from Dieng, K3 group were treated with C. pubescens extract from Cangar, and K4 group were treated with policresulen preparations. At the end of fifth day, the rats were sacrificed and the mandibular gingival mucosa were collected for histologist preparations. The result of this study shows that K3 group has the thickest gingival epithel layers while there is no significant different among four group for the thikness gingival epithel layers